Kinetics. - Benthall, Jonathan; Crosby, Theo; Popper, Frank (London : Hayward Gallery, 1970)
Antonakis, Stephen ; Benton, Fletcher ; Biasi, Alberto ; Boriani, Davide ; Boto, Martha ; Breer, Robert ; Bury, Pol ; Calder, Alexander ; Calos, Nino ; Carder, Malcolm ; Cheney, Al ; Colombo, Gianni ; Cooper, Mike ; Demarco, H.R. ; Garcia-Rossi, Horacio ; Graevenitz, Gerhard von ; Grant, Keith ; Greenham, Lily ; Hayden, Michael ; Hoogenboom, Ser ; Jansma, Arie ; Janz, Robert ; Jones, Howard ; Kaine, John ; Kosice, Gyula ; Kowalski, Piotr ; Kramer, Harry ; Leonelli, Dante ; Parc, Julio Le ; Lijn, Liliane ; Logan, Peter ; Lurker, Ernst ; Luther, Adolf ; Mack, Heinz ; Malina, Frank Joseph ; Mallory, Ronald ; Marijs, Willem ; Martin, Barry ; Massironi, Manfredo ; Mattox, Charles ; McClanahan, Preston ; McKinnon, Michael ; Megert, Christian ; Morellet, François ; Müller, Hans Walter ; Munari, Bruno ; Paik, Nam June ; Piene, Otto ; Prentiss, Chuck ; Pye, William ; Rickey, George ; Rieveschl, Gary T. ; Salvadori, Marcello ; Schöffer, Nicholas ; Seawright, James ; Staakman, Ray ; Takis ; Tinguely, Jean ; Uecker, Günther ; Vardanega, Gregorio ; de Vecchi, Gabriele ; Verpoorten, Frans ; Vilder, Roger ; Willats, Stephen ; Wynter, Bryan ; Van Zutphen, Johan
biografie
Kinetics, Hayward Gallery, London, 25 September to 22 November 1970
Engels
kunstcatalogus